Chapter Agentive Phenomenology - Mylopoulos, Myrto (Oxford University Press, 2020)
This chapter reflects on questions about the nature and sources of agentive phenomenology-that is, the set of those experience-types associated with exercises of agency, and paradigmatically with intentional actions. The discussion begins with pioneering work in psychology and neuroscience that dates to the early 1980s. Much of the current work on agentive phenomenology in both psychology and philosophy draws motivation from this work, and the questions it raises. After discussing empirical work relevant to agentive phenomenology, the chapter considers its nature, covering questions about the scope of agentive phenomenology, about its relationship to other types of experiences, about the best way to characterize aspects of agentive phenomenology, and about the function of various types of agentive experience.